El Salvador Financial Sector Assessment Program Development Module : Non-Bank Savings and Credit Institutions - World Bank (World Bank, Washington, DC, 2017)
This Technical Note was prepared in the context of a World Bank Financial Sector Assessment Program mission in the Republic of El Salvador in March 2016. This FSAP Development Module focuses on (i) financial systems issues, including competition and efficiency; (ii) financial inclusion and non-bank financial institution issues, (iii) public sector banks, (iv) financial system infrastructure, including payments, remittances transfers, and credit information systems; (v) capital market and private pensions development issues; and (iv) insurance. This note is arranged as follows: Section I gives the Background and Current Situation. Section II describes Extension of the Regulatory Perimeter and Section III discusses about Select Latin American Experiences on Supervision Of NBSCI. The document contains technical analysis and detailed information underpinning the FSAP assessment’s findings and recommendations. Further information on the FSAP program can be found at www.worldbank.org/fsap.